Evaluation of Bi as internal standard to minimize matrix effects on the direct determination of Pb in vinegar by graphite furnace atomic absorption spectrometry using Ru permanent modifier with co-injection of Pd/Mg(NO3)(2) - de Oliveira, Silvana Ruella; Gomes Neto, José Anchieta [UNESP] (Elsevier B.V., 2007)
Bismuth was evaluated as an internal standard for the direct determination of Pb in vinegar by graphite furnace atomic absorption spectrometry using Ru as a permanent modifier with co-injection of Pd/Mg(NO3)(2). The correlation coefficient of the graph plotted from the non-nalized absorbance signals of Bi versus Pb was r=0.989. Matrix effects were evaluated by analyzing the slope ratios between the analytical curve, and analytical curves obtained from Pb additions in red and white wine vinegar obtained from reference solutions prepared in 0.2% (v/v) HNO3, samples. The calculated ratios were around 1.04 and 1.02 for analytical curves established applying an internal standard and 1.3 and 1.5 for analvtical curves without. Analytical curves in the 2.5-15 pg L-1 Pb concentration interval were established using the ratio Pb absorbance to Bi absorbance versus analvte concentration, and typical linear correlations of r=0.999 were obtained. The proposed method was applied for direct determination of Pb in 18 commercial vinegar samples and the Pb concentration varied from 2.6 to 31 pg L-1. Results were in agreement at a 95% confidence level (paired t-test) with those obtained for digested samples. Recoveries of Pb added to vinegars varied from 96 to 108% with and from 72 to 86% without an internal standard. Two water standard reference materials diluted in vinegar sample were also analyzed and results were in agreement with certified values at a 95% confidence level. The characteristic mass was 40 pg Pb and the useful lifetime of the tube was around 1600 firings. The limit of detection was 0.3 mu g L-1 and the relative standard deviation was <= 3.8% and <= 8.3% (n = 12) for a sample containing, 10 mu L-1 Pb with and without internal standard, respectively. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: lead; vinegar; graphite furnace atomic absorption spectrometry; Bismuth internal standard; RU permanent modifier